Comparative evaluation of Egg Quality Parameters of Kadaknath and Vanaraja Chicken in Intensive Farming System - Pathak, SS; Tamuli, U; Khargaria, S; Bordolai, G; Khuman, LS; Chabukdhara, P; Gagoi, A; Rajbhogshi, P; Boruah, K (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
In the present study , a total of 60 eggs were assessed for egg quality parameters of Kadaknath and Vanaraja chicken reared under deep litter farming system . All chickens were provided uniform diet of Chick (0-8 weeks), Grower (9-20 weeks) and Layer (above 20 weeks) ration. Except for the shape index, the internal egg quality parameters were significantly (P
Keywords: Kadaknath; Vanaraja,; chickens; egg quality; litter